2006
DOI: 10.5194/angeo-24-887-2006
|View full text |Cite
|
Sign up to set email alerts
|

IMF effect on sporadic-E layers at two northern polar cap sites: Part I – Statistical study

Abstract: Abstract. In this paper we investigate the relationship between polar cap sporadic-E layers and the direction of the interplanetary magnetic field (IMF) using a 2-year database from Longyearbyen (75.2 • CGM Lat, Svalbard) and Thule (85.4 • CGM Lat, Greenland). It is found that the MLT distributions of sporadic-E occurrence are different at the two stations, but both are related to the IMF orientation. This relationship, however, changes from the centre of the polar cap to its border. Layers are more frequent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Our results are consistent with previous ground‐based observations as summarized by Kirkwood and Nilsson []. The nighttime CS occurrence is probably due to the corresponding small‐scale electric field variation, which is assumed to be the source of E s in polar region [ Kirkwood and Nilsson , ; Mathews , ; Voiculescu et al ., ]. For comparison, we also embedded the polar electric potential contour calculated from Weimer05 model in the figure [ Weimer , ].…”
Section: Cycle Slip Occurrence In E Region and Its Relation To Sporadmentioning
confidence: 99%
“…Our results are consistent with previous ground‐based observations as summarized by Kirkwood and Nilsson []. The nighttime CS occurrence is probably due to the corresponding small‐scale electric field variation, which is assumed to be the source of E s in polar region [ Kirkwood and Nilsson , ; Mathews , ; Voiculescu et al ., ]. For comparison, we also embedded the polar electric potential contour calculated from Weimer05 model in the figure [ Weimer , ].…”
Section: Cycle Slip Occurrence In E Region and Its Relation To Sporadmentioning
confidence: 99%
“…Later, MacDougall and Jayachandran (2005) argued that Es layers observed at 77 • CGM Lat could be explained by a two-step mechanism involving horizontal convergence of ionisation followed by vertical convergence, both under the effect of electric field. Voiculescu et al (2006) and Nygrén et al (2006) investigated the statistical relation of polar cap electric field and the occurrence of sporadic E at two polar cap sites, Longyearbyen and Thule, using electric fields given by the APL model based on IMF data (Ruohoniemi and Greenwald, 1996). It was shown in these studies that the layer occurrence was in most cases in reasonable agreement with the electric field theory of sporadic E.…”
Section: Introductionmentioning
confidence: 89%
“…They form by vertical convergence of ionospheric plasma caused by appropriate structures in the vertical shear of neutral wind and/or favourable electric field directions (Nygrén et al, 1984;Whitehead, 1989;Mathews, 1998;Kirkwood and Nilsson, Correspondence to: T. Nygrén (tuomo.nygren@oulu.fi) 2000). It has been shown that Es layers are observed even inside the polar cap, despite the very high inclination of the geomagnetic field there (Wan et al, 1999;MacDougall et al, 2000a;Voiculescu et al, 2006). Experimental and theoretical findings support the idea that the electric field is the main driving factor of Es layer formation within the polar cap (Parkinson et al, 1998;Wan et al, 1999;Bedey and Watkins, 2001;MacDougall and Jayachandran, 2005;Nygrén et al, 2006), although there are calculations showing that gravity waves might also play a role (MacDougall et al, 2000b).…”
Section: Introductionmentioning
confidence: 95%
“…In the first paper of this series (Voiculescu et al, 2006; hereafter referred to as Paper I), the relation of the IMF and sporadic E at two polar cap sites, Longyearbyen and Thule, were studied. In this second paper, we investigate the same data in view of the electric field mechanism of layer generation.…”
Section: Introductionmentioning
confidence: 99%
“…This paper is the second in a series on a study of the link between IMF and sporadic-E layers within the polar cap. In Paper I (Voiculescu et al, 2006), an analysis of the sporadic-E data from Thule and Longyearbyen was presented. Here we concentrate on the electric field mechanism of sporadic-E generation.…”
mentioning
confidence: 99%